2010
DOI: 10.1186/1751-0759-4-6
|View full text |Cite
|
Sign up to set email alerts
|

The Thai version of the PSS-10: An Investigation of its psychometric properties

Abstract: BackgroundAmong the stress instruments that measure the degree to which life events are perceived as stressful, the Perceived Stress Scale (PSS) is widely used. The goal of this study was to examine the psychometric properties of a Thai version of the PSS-10 (T-PSS-10) with a clinical and non-clinical sample. Internal consistency, test-retest reliability, concurrent validity, and the factorial structure of the scale were tested.MethodsA total sample of 479 adult participants was recruited for the study: 368 me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
149
3
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(178 citation statements)
references
References 13 publications
22
149
3
4
Order By: Relevance
“…Mexican Spanish [5], Japanese [6], Chinese [7], Thai [8], Turkish [9], Arabic [10], Urdu (Pakistan language) [11], Lithuanian [12], Danish, Brazilian, Korean, Russian, Polish, Bulgarian, Hungarian, Italian, Hebrew [13]. Those international studies suggest that the psychometric properties of the scale are satisfactory.…”
Section: Resultsmentioning
confidence: 99%
“…Mexican Spanish [5], Japanese [6], Chinese [7], Thai [8], Turkish [9], Arabic [10], Urdu (Pakistan language) [11], Lithuanian [12], Danish, Brazilian, Korean, Russian, Polish, Bulgarian, Hungarian, Italian, Hebrew [13]. Those international studies suggest that the psychometric properties of the scale are satisfactory.…”
Section: Resultsmentioning
confidence: 99%
“…Quando os itens da PSS-10 são separados em dois fatores, estes apresentam correlações de 0,51 a 0,69, o que sugere uma moderada covariância entre ambas as dimensões (Reis et al, 2010;Roberti et al, 2010;Wongpakaran & Wongpakaran, 2010). O fator retido apresentou adequada consistência interna, e todos os itens da PSS-10 apresentaram cargas fatoriais de adequada magnitude (> 0,37).…”
Section: Tabela 1 Cargas Fatoriais Dos Itens Da Pss-10unclassified
“…Os resultados da análise de fatores comuns e da análise paralela permitiram identifi car a dimensionalidade da PSS-10, apontando uma solução unifatorial como a mais representativa dos dados. Entretanto, é importante salientar que a dimensionalidade da PSS-10 não é um consenso na literatura (Leung et al, 2010;Reis et al, 2010;Roberti et al, 2010;Wongpakaran & Wongpakaran, 2010).…”
Section: Considerações Finaisunclassified
See 1 more Smart Citation
“…Scores can range from 0 to 40, with higher scores indicating higher levels of perceived stress (Cohen & Williamson, 1988). Internal consistency for the PSS-10 has ranged from .78 to .91, and test-retest reliability ranged from .72 to .88 (Cohen & Williamson, 1988;Mitchell, Crane, & Kim, 2008;Reis, Hino, & Rodriguez-Añez, 2010;Remor, 2006;Wongpakaran & Wongpakaran, 2010). Criterion validity between the PSS-10 and the Medical Outcomes Study short form (MOS-SF36) mental component showed concurrent validity correlations of .70 (Mitchell, Crane, & Kim, 2008).…”
Section: Methodsmentioning
confidence: 99%